The The Creation of an Ottoman Turkish Psalter. Ali Ufkî’s (Bobovius) Mezmûriyye (ca. 1665) and Maciej Rybiński’s Psalmy Dawidowe (1608) - Pawlina, Agata (The Biblical Annals, 2023)
Wojciech Bobowski is better known in international academia under the Latinised version of his name: Albertus Bobovius and by his Turkish name: Ali Ufki. Most probably, he was born in Lviv, ca. 1610 and died in Constantinople, ca. 1675. He left for posterity numerous works that today we would classify as belonging to several fields of the humanities: musicology, linguistics, religious studies, cultural studies, political history and even ethnography. His best-known works include one of the earliest translations of the Bible into Turkish (1662–1664), an influential treatise on Islam (1690), a description of the Topkapı Palace (1665) – the main seat of the Ottoman sultan, where he lived and worked as a court musician – and collection of more than 500 Ottoman Turkish musical pieces written in European stave notation (ca. 1640–1650). In this paper, the author first presents outcomes of her current archival research on Bobowski’s early life in the Polish-Lithuanian Commonwealth. Then, she demonstrates the possibility that when working on Mezmuriyye – the Ottoman Turkish psalter, Ali Ufki took inspiration from the Polish translation of the Genevan Psalter from French by Maciej Rybiński, an influential bishop of the Reformed Church in the 17th-century Poland. This theory is based on the analysis of linguistic content of French, Polish and Ottoman Turkish lyrics, as well as the striking visual resemblance of Bobowski’s Mezmuriyye and one specific old-print of Rybiński’s Psalmy Dawidowe na melodie francuskie uczynione published in 1608.